48.2k views
2 votes
(9r²+5r-11) - (-2r²+9r-8)

2 Answers

1 vote

Answer:

11r²-4r-3

Explanation:

soo,, now firstly change the signs of 2nd expression

so,

9r²+5r-11+2r²-9r+8

now

we will combine the same terms like , see next step

9r²+2r²+5r-9r-11+8

11r²-4r-3

User Hard Spocker
by
4.7k points
2 votes

Good evening ,

Answer:

___________________________________________

(9r²+5r-11) - (-2r²+9r-8) = 11r² -4r - 3

___________________________________________

Explanation:

(9r²+5r-11) - (-2r²+9r-8) =

= (9r²+5r-11) + 2r²- 9r + 8

= 9r²+5r-11 + 2r²- 9r + 8

= (9r²+2r²)+ (5r-9r) + (8-11) Just put like terms together.

= 11r² -4r - 3.

:)

User CrazyChucky
by
4.9k points